Day 2 Thu, February 25, 2016 2016
DOI: 10.2118/179001-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Results and Experimental Comparative Analysis of Sodium and Nonsodium Chelant-Based HF Acidizing Fluids for Sand Control Operations

Abstract: Field results and laboratory data are presented for the purpose of identifying best practices for two different acidizing fluids based on chelating agents containing hydrofluoric (HF) acid employed in clean-up treatments in high-rate water pack completions (HRWP). The HF fluids are a newly introduced aminopolycarboxylic acid (APCA), pH 2.5 to 3 that contains sodium ions, and an established hydroxycarboxylic acid (HCA) fluid, pH 3, sodium-free. Flow testing was conducted at the anticipated bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For additional information on the use of APCA-Na/HF acid fluid, the interested reader is referred to LaBlanc et al (2016) and Reyes et al (2016). For additional information on the use of APCA-Na/HF acid fluid, the interested reader is referred to LaBlanc et al (2016) and Reyes et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…For additional information on the use of APCA-Na/HF acid fluid, the interested reader is referred to LaBlanc et al (2016) and Reyes et al (2016). For additional information on the use of APCA-Na/HF acid fluid, the interested reader is referred to LaBlanc et al (2016) and Reyes et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Ammonium salts of chelating agents should be utilized in hydrofluoric (HF) acid applications to avoid fluorosilicate precipitation. While this is true for common chelating agents, recent research has shown that chelating agents can be designed to overcome the problem of fluorosilicate precipitation with non-ammonium chelating agents [30,31].…”
Section: Subsurface Formations Containing Sandstone Mineralsmentioning
confidence: 99%
“…Following the successful laboratory experiments, chelating agents have therefore been applied to field treatments and have been shown to be able to restore permeability to damaged formations [30,31,37]. However, authors have described different methods of applying chelating agent treatments.…”
Section: Subsurface Formations Containing Sandstone Mineralsmentioning
confidence: 99%